266RBM20-dependent regulation of organized myofilament structure and titin splicing in induced pluripotent stem cell-derived cardiomyocytes from patients with dilative cardiomyopathy. (15th July 2014) - Streckfuss-Boemeke, K; Fischer, C; Stauske, M; Perret, A; Oezcelic, C; Wagner, S; Maier, L; Hasenfuss, G; Guan, K
Abstract: Purpose: The ability to generate patient-specific human induced pluripotent stem cells (ps-iPSCs) provides a unique opportunity for modeling heart disease. Dilated cardiomyopathy (DCM) is due to a progressive enlargement of the heart leading finally to heart failure. Mutations in many genes have been implicated in the pathogenesis of DCM including the RNA-binding motif 20 (RBM20). We aimed to generate iPSCs from DCM patients with a RBM20 mutations, and to analyze the functionality and cell biology of cardiomyocytes derived from these ps-iPSCs (ps-iPSC-CM) with regard to the cardiac DCM phenotype. Methods and Results: Dermal fibroblasts from two patients (34y; 75y) with DCM harboring different RBM20 mutations were reprogrammed to ps-iPSCs via lentiviral infection using the STEMCCA system. The ps-iPSCs show pluripotent characteristics by expressing pluripotency markers on mRNA and protein level similar to human embryonic stem cells. Furthermore, bisulfite sequencing analysis showed that the OCT4 and NANOG promoters were significantly demethylated in ps-iPSCs compared to their parental cells. In addition, the generated RBM20-iPSCs are able to differentiate in vitro and in vivo into derivatives of all three germ layers. The cardiac in vitro differentiation efficiency into beating cardiomyocytes of the RBM20-iPSCs is similar to control iPSCs. Electrophysiological studies showed that under basal conditions ps-iPSC-CM exhibited spontaneous action potentials characteristic for pacemaker-, atrial-, ventricular- and Purkinje-like cells in a similar manner as control iPSC-CM. Using Fast Fourier Transformation the sarcomere-associated periodic signal amplitude was analyzed for α-actinin. A significant higher percentage of RBM20-iPSC-CM showed abnormal sarcomeric α-actinin distribution compared to control CM, suggesting disorganized myofilament structure. But no significant difference was observed in cell size between RBM20-iPSC-CMs and control cells. Further, we found a different isoform expression pattern of the cardiac titin in the mutant ps-iPSC-CM compared to the control cells. This demonstrates a RBM20-dependent regulation of organized myofilament structure and titin splicing in an in vitro ps-DCM-iPSC-model. Conclusion: We demonstrate that iPSC-derived cardiomyocytes from young and old DCM patients harboring a RBM20 mutation recapitulate the abnormalities that were found in individuals with DCM caused by the same mutation. The differentiated cardiomyocytes may be used for individual drug testing and development of novel treatments for this inherited disorder.